Reflecting self: An interactive mirror study - Wu, Y.; Chang, T.; Liao, M.; Datta, Sambit (2016)
Immersive environment provides a virtual environment immersion experience for the user, and allow users in-depth experience. In this study through research "self- reflecting" and "selfreflecting during interaction with the space environment" by entity makeup table for discussion. Makeup table reflect the role of people and the surrounding environment. We found the style selected by the user, often conform to the user's external style, and does not because of the age limit the user to interact with curiosity. We also found that in addition to the female user, make up table will also trigger young men of curiosity, they will close to observation and interaction with the table. Finally, we have statistical distribution of general user preferences. We also in accordance with the user's behavior, revised interactive processes, make recommendations when designing immersive environments.